Optimal Fall Protection System Selection Using a Fuzzy Multi-Criteria Decision-Making Approach for Construction Sites - Jin, Haifeng; Goodrum, Paul M. (Applied sciences, 2021)
Construction falls are a leading cause of fatalities in almost every construction industry around the globe, and fall protection systems are the key measures to ensure the safety of labor crews. This study develops a fuzzy multi-criteria decision-making model integrating analytical hierarchy process, fuzzy set theory and Technique for Order Preference by Similarity to Ideal Solution approach to analyze the overall performance of various fall protection plans for construction projects, which focuses on evaluation and selection of the appropriate protection plan considering the most influential safety, productivity, and economy factors. Results show that the optimal plan can be effectively identified and determined among all potential alternatives. Besides, the model overcomes the shortcoming of weight value uncertainty and ambiguous decision information through membership function calculations. As a result, it provides guidance for the improvement of construction performance, intending to minimize fall risks, improve labor productivity, and save economical cost on the jobsites.